African countries from the Pasteur Network reexamine their syndromic sentinel surveillance system associated with household contact within the AFROSCREEN program - Tejiokem, Mathurin Cyrille; Barry, Aliou; Ratovoson, Rila; Yambiyo, Brice; Hamidou Lazoumar, Ramatoulaye; Herrant, Magali; Madaha, Estelle; Richard, Vincent (Frontiers in Public Health, 2024)
Surveillance to better detect and respond to new pathogens remains a major challenge for global public health. The Pasteur Network recently held a brainstorming workshop located in Cameroon attended by Pasteur epidemiological teams from Niger, Central African Republic (CAR), Cameroon, Senegal, and Madagascar to discuss how the Pasteur Network in Africa could use the lessons of COVID-19 to set-up a pilot sentinel surveillance scheme given its expertise and involvement during the pandemic. The possibility of coupling sentinel syndromic and biological surveillance already implemented for influenza surveillance with the recent sequencing capacity put in place by the AFROSCREEN program prompted us to consider strengthening surveillance tools to target “Pathogen X” detection in Africa. The perspective project provided by the Pasteur Network teams and shared with other partners of the AFROSCREEN program will target strengthening of the diagnosis of severe acute respiratory infections (IRAS) and the surveillance of IRAS, the evaluation of the impact of SARS-CoV-2 on the epidemiology of IRAS, and the addition of the detection of new pathogens, called “Pathogen X,” based on sequencing capacity and epidemiological criteria from One Health approaches.